Unlocking Dignity: Self-Worth and Life Satisfaction through the Lens of Female Persons Deprived of Liberty - Ciara Maricar M Tan (Advanced Qualitative Research, 2024)
The study aimed to explore the lived experiences of female PDLs in relation to self-worth and life satisfaction, as most incarcerated mothers find it challenging to adjust to their lives and find balance in maintaining their relationships. To fully understand self-worth and life satisfaction from their perspectives, their past experiences, present circumstances and plans were discussed. Seven (7) incarcerated mothers who gave birth from years 2020-2024, ranging from 20-35 years old, were interviewed. The theories utilized were Self-Worth Theory and Life Satisfaction as an aspect of Subjective Well-being. Interpretative Phenomenological Analysis was used, wherein the participants were interviewed via semi-structured interview guide questions. This study generated 11 superordinate themes which mainly centered on their education, career, status, children and family. From these findings, the author came up with supplemental programs, otherwise collectively called the MAC Program, that could help the incarcerated mothers, their children, their families and the jail authorities, both while the PDLs were in jail and after being re-integrated into their communities. It is a holistic program which includes activities for Psychological Wellbeing and Mental Health Services; Educational Assessment and Career Development; Family Support System; and Motherhood and Parenting Support Program. Investigating the self-worth and life satisfaction of the female PDLs can help assess how to better manage the PDLs as well as avoid re-incarceration. Equipping the female PDLs with the proper knowledge, skills, and behaviour can help them and their families live a better and renewed life once they get released from the jail facilities.